PENGARUH EFIKASI DIRI, DUKUNGAN ORANG TUA, DAN LINGKUNGAN SEBAYA TERHADAP KEPUTUSAN MELANJUTKAN STUDI KE PROGRAM STUDI PENDIDIKAN EKONOMI - Nurhikmat, Nurhikmat; Gumilar, Gugum; Kurniawan, Kurniawan (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2026)
This study aims to analyze the influence of self-efficacy, parental support, and peer environment on students’ decisions to pursue further study in the Economic Education Study Program. The study was motivated by the relatively low level of student interest in teacher education programs amid increasing participation in higher education, indicating that educational decisions are influenced not only by academic ability but also by psychological and social factors. This research employed a quantitative approach using a survey method administered to eleventh-grade students of public senior high schools in Tasikmalaya Regency. The sample consisted of 119 respondents, determined through G*Power analysis. The data were analyzed using multiple linear regression to examine both partial and simultaneous effects among the variables. The findings indicate that self-efficacy does not have a significant effect on the decision to pursue further study in the Economic Education Study Program. The peer environment has a positive effect on the decision to pursue further study in the Economic Education Study Program, whereas parental support has a statistically significant negative effect. Simultaneously, the three variables collectively influence the decision to pursue further study, with the peer environment emerging as the most dominant variable